Natural History of Polymerase Gamma–Related Ataxia. Issue 11 (20th July 2021) - Bender, Friedemann; Timmann, Dagmar; van de Warrenburg, Bart P.; Adarmes‐Gómez, Astrid D.; Bender, Benjamin; Thieme, Andreas; Synofzik, Matthis; Schöls, Ludger
ABSTRACT: Background: Mutations in the mitochondrial DNA polymerase gamma are causing a wide phenotypic spectrum including ataxia as one of the most common presentations. Objective: The objective of this study was to determine the course of disease of polymerase gamma–related ataxia. Methods: In a prospective natural history study, we assessed 24 adult ataxia patients with biallelic polymerase gamma mutations for (1) severity of cerebellar dysfunction using the Scale for the Assessment and Rating of Ataxia score, (2) presence of nonataxia signs using the Inventory of Non‐Ataxia Symptoms, (3) gray‐ and white‐matter changes in brain MRI, and (4) findings in nerve conduction studies. Results: Assessment included follow‐up visits up to 11.6 years. The Scale for the Assessment and Rating of Ataxia showed a mean annual increase of 1.02 ± 0.78 points/year. Disease progression was faster in patients with age at onset ≤ 30 years (1.5 Scale for the Assessment and Rating of Ataxia points/year) than with later onset (0.5 points/year); P = 0.008. The Inventory of Non‐Ataxia Symptoms count increased by 0.30 ± 0.4 points/year. External ophthalmoplegia, brain stem oculomotor signs, areflexia, and sensory deficits were the most common nonataxic features. On MRI cerebellar atrophy was mild. T2 signal alterations affected mostly cerebellar white matter, middle cerebellar peduncles, thalamus, brain stem, and occipital and frontal white matter. Within 4 years, progression was primarily observed in the context of repeated epileptic seizures. Nerve conduction studies revealed axonal sensory peripheral neuropathy with mild motor nerve involvement. Exploratory sample size calculation implied 38 patients per arm as sufficient to detect a reduction of progression by 50% in hypothetical interventions within a 1‐year trial. Conclusion: The results recommend the Scale for the Assessment and Rating of Ataxia as a primary outcome measure for future interventional trials in polymerase gamma–related ataxia. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society